Exploring the impact of Firm-Level Corporate Governance Challenges on Sustainable Development Goals (SDGs) in a Developing Economy - Makwara, Tendai (Research Collaboration Community (RCC), 2024)
The impact of firm-level corporate governance challenges on sustainable development requires attention, particularly in developing countries. This qualitative study explores factors contributing to South African firms' poor CG performance and the implications of firm-level CG challenges towards attaining SDGs in South Africa. It employs a rapid review methodology to search and review selected articles systematically. Content analysis is used to draw findings. Results reveal that historical, economic, lack of critical scholarship and weak regulatory enforcement and oversight factors affect South African corporate governance practices. Notably, a lack of reform in the corporate governance architecture underpins most of the challenges firms experience regarding corporate governance practices. These results can be linked to slow progress towards realising sustainable development goals (SDG) targets from achieving socioeconomic equality, board diversity, jobs, poverty alleviation and justice for all. This study contributes to scholarship on the intersectionality between CG, SDGs, and existing challenges that restrict the business sector from fully contributing to national development. In South Africa, the study also reviews progress towards strengthening the CG fabric in the post-apartheid era.